ANALISIS USAHA TANI DAN KEMAMPUAN MEMBAYAR KREDIT PETANI KARET EKS UPP TCSDP TALUK KUANTAN SUB UNIT KUANTAN MUDIK - Lovia C. Fransiska Manik; Syaiful Hadi; Didi Muwardi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aimed to analyze the farming and the ability to pay the loan Ex UPP TCSDP Taluk Kuantan sub units Kuantan Mudik. This research was conducted by survey method where a representative sample is taken from the three villages, each village with purposive sampling (intentionally) as many as 10 respondents, so the total respondents as many as 30 respondents. The results showed that the productivity of rubber plantations Ex TCSDP as much as 2989.57 kg ojol / ha / year and the plantations of non TCSDP as much as 2136.46 kg ojol/ ha / year. In 1997, average loan principal is Rp. 856,685.17, lending (12% / year) is Rp. 1,384,079.16 and total credit debt of Ex TCSDP farmers until 1997 was Rp. 2,240,764.33. In 2015, the average interest rate that must be paid the farmer is Rp. 3,234,519.12 and the average loan was repaid farmer is Rp. 703,130.09. The average credit debt that must be paid by the farmer is Rp. 3,388,074.20. Rubber of Ex TCSDP plantation revenue of Rp. 4,071,245.83 while the farmer household expenditure is Rp. 26,118,133.33 so that farmers can not afford to pay for the credit. But when viewed from the total income (household income) is Rp. 27,857,456.67 larger than the household expenses by 22 (73.33%) of farmers unable to pay the loan Former UPP TCSDP. Keywords : Rubber Farmers , Credit , Productivity , TCSDP